Cutaneous blastomycosis : A Rare Case (Northern International Medical College Journal, 2017)
Cutaneous blastomycosis lesion is most often originate from a Primary pulmonary infection which disseminates through the blood or lymphatics to involve the skin. During the manifestations of cutaneous lesion in case of secondary blastomycosis, the primary pulmonary infection is frequently subclinical. Here we report a case that illustrates the difficulty in diagnosing a case of cutaneous blastomycosis.Northern International Medical College Journal Vol.8(1) July 2016: 189-191